Dual-biprism-based single-camera high-speed 3D-digital image correlation for deformation measurement on sandwich structures under low velocity impact - Zhang, Weiling; Xu, Mengqiao; Yuan, Tianyu; Li, Wenjing; Dai, Xiangjun; Zhang, Zhongwei; Yun, Hai; Wang, Yanxia (Reviews on advanced materials science, 2023)
Herein, a single-camera stereo digital image correlation (DIC) method is developed for dynamic deformation measurement, and a dual-biprism high-speed stereo camera system is proposed to capture surface images. Then, full-field displacement and strain distributions are obtained after correlation and differential calculation using the stereo-DIC algorithm. After a typical experiment is performed to verify the accuracy of the proposed system, full-field displacement and strain distributions of sandwich panels subjected to low-velocity impacts are determined. These results show that the proposed system is an efficient and convenient tool for dynamic deformation measurement.